Perancangan Sistem Informasi Administrasi Transaksi E-Commerce Menggunakan Metode RAD dan MVC Framework Laravel Pada KOMA Collection - Diki Permana; Kussigit Santosa (CV. Multi Kreasi Media, 2024)
E-commerce transaction administration information system plays a crucial role in the operation of online businesses. This research aims to design an efficient and reliable e-commerce transaction administration information system using the Rapid Application Development (RAD) method and MVC (Model-View-Controller) framework Laravel at KOMA Collection. The RAD method is employed to accelerate the system development process and ensure active user involvement in the design phase. Meanwhile, the MVC framework Laravel provides a clear and organized structure for developing PHP-based web applications. This study combines qualitative and quantitative approaches in data collection and analysis. Data are gathered through interviews with the owner of KOMA Collection, observations of the existing transaction administration processes, and surveys conducted among potential users. The result of this research is the design of an e-commerce transaction administration information system that includes modules for user registration, product management, shopping cart, payment, and transaction history. Additionally, the system is equipped with inventory management and sales reporting features to support efficiency and business decision-making. The implementation of this e-commerce transaction administration information system is expected to assist KOMA Collection in improving operational efficiency, enhancing user experience, and strengthening competitiveness in the e-commerce industry. Furthermore, the findings of this research contribute to the development of better e-commerce transaction administration information systems in the future.